Pengaruh Brand Trust, Cita Rasa, dan Inovasi Produk terhadap Minat Beli Konsumen pada CFC Stasiun Kediri - Aprilinda Setiana; Zaenul Muttaqien; Ahmad Jauhari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the influence of Brand trust (X1), Taste (X2), and Product Innovation (X3) on Consumer Purchase Intention (Y) at CFC Stasiun Kediri. The research adopts a quantitative approach with data collected through questionnaires and processed using SPSS 25. The sample was determined using purposive sampling and the Hair et al. formula, resulting in a total of 105 respondents. The analytical techniques employed include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, and Coefficient of Determination (R²). The results show that Brand trust has a significant effect on consumer purchase intention at CFC Stasiun Kediri with a significance value of 0.000 < 0.05. Taste has a significant effect on consumer purchase intention with a significance value of 0.008 < 0.05. Product Innovation also has a significant effect on consumer purchase intention with a significance value of 0.000 < 0.05. Furthermore, Brand trust, Taste, and Product Innovation simultaneously have a significant effect on consumer purchase intention at CFC Stasiun Kediri.